Automatically Generated Visual Profiles of Code Solutions as Feedback for Students - Jakub Swacha (Information, 2022)
Providing students feedback on their exercise solutions is a crucial element of computer programming education. Such feedback can be generated automatically and can take various forms. This paper introduces and proposes the use of visual profiles of code solutions as a form of automatically generated feedback to programming students. The visual profiles are based on the frequency of code elements belonging to six distinct classes. The core idea is to visually compare a profile of a student-submitted solution code to the range of profiles of accepted solutions (including both reference solutions provided by instructors and solutions submitted by students who successfully passed the same exercise earlier). The advantages of the proposed approach are demonstrated on a number of examples based on real-world data.